Description and primary validation of a game understanding test in volleyball - Häyrinen, M.; Blomqvist, M.; Luhtanen, P.; Norvapalo, K. (5th World Congress of Performance Analysis of Sport, 2001)
The purpose of this study was to develop a valid and reliable video-based test to evaluate game understanding in volleyball. Two groups served as subjects; a class of comprehensive school students (novices, 13.9±0.3 years, 17 girls and 15 boys) and a group of high school students from the Finnish Volleyball Association's Training Centre (experts, 17.7±1.0 years, 9 girls and 15 boys). The test consisted of 24 different sequences, which were video sequences from actual match situations. The Delphi techniques were used to select these sequences out of 30 situations by four volleyball experts. Each situation started with a still frame (3 seconds) and continued with a sequence of play (2-20 seconds). Finally, a still frame representing three alternatives for the player's responses was shown for 10 seconds. Based on this still frame the students had to decide what to do, and in addition, they had 40 seconds to select two relevant arguments from the list of 7-9 written arguments to verify their decision. Each player received three scores from the test; selected options (SEO), selected argument options (ARO) and total amount of points (TAP) (maximum scores 48, 72 and 120 points, respectively). Students made the test two times during their normal school or training hours. The time interval between the test and retest was 5-14 days. The scores were as follows: novices SEO 23.4±3.3, ARO 11.9±4.2, TAP 35.3±5.9 and experts 36.7±5.9, 41.9±6.0, 78.6±8.6, respectively. An independent t-test was applied to detect differences between the groups and the results showed statistically significant (p<.001) differences for all scores. Test-retest method (intraclass correlation, ICC) was applied to evaluate reliability of the test. ICC for TAP was 0.51 (p<.01) for novices and 0.42 (p<.05) for experts. These results show that this test might be suitable for measuring game understanding in volleyball, but more material from different age and skill level groups has to be collected to validate this test thoroughly.